Evaluation of some Rhizobium strains in tropical forage legumes - Escuder, Ana Maria Quadrelli de (Pesquisa Agropecuaria Brasileira, 2014)
In a field experiment carried out in a Dark Red Latosol Soil of a just opened Cerrado area, the Rhizobium strains BR 1a, BR 23a, C 101 and C 102, and P 105, in the leguminous species Stylosanthes guianensis IRI 1022, Macroptilium atropurpureum cv. Siratro, Centrosema pubescens cv. Deodoro, Glycine wightil cv. Tinaroo respectively as to dry matter production and total N accumulation, were evaluated. According to the analysis the soil received liming and a basic fertilization with P, K, S and the microelements B, Zn, Cu and Mo added. The experimental desing was a randomized complete block desing with four replications. The treatments were: a) inoculated; b) three nitrogen levels and c) blank with neither inoculation nor nitrogen. In a growth period of seventeen months there were four cuttings to evaluate dry matter production and total nitrogen accumulation. There were no significant differences between treatments, that is, there was no effects of inoculation or addition of nitrogen fertilizer on those characteristics. Stylosan thes showed the highest dry matter production (P<0.01) among the legume species tested while Centrosema presented the highest levels of total nitrogen accumulation (P<0.05) in the upper leaves.